2019
DOI: 10.1002/dneu.22713
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological correlates of amyloid PET imaging in Down syndrome

Abstract: Down syndrome (DS) results in an overproduction of amyloid‐β (Aβ) peptide associated with early onset of Alzheimer's disease (AD). DS cases have Aβ deposits detectable histologically as young as 12–30 years of age, primarily in the form of diffuse plaques, the type of early amyloid pathology also seen at pre‐clinical (i.e., pathological aging) and prodromal stages of sporadic late onset AD. In DS subjects aged >40 years, levels of cortical Aβ deposition are similar to those observed in late onset AD and in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 131 publications
(259 reference statements)
5
35
0
Order By: Relevance
“…Previous studies showed that amyloid deposits of AD and DS brains are heterogeneous, and could contain post-translationally modified and truncated Aβ variants [ 16 , 18 23 , 29 , 31 , 35 , 36 , 39 , 42 , 54 , 61 , 76 ]. Some of these modified Aβ species are also observed in the brains of transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that amyloid deposits of AD and DS brains are heterogeneous, and could contain post-translationally modified and truncated Aβ variants [ 16 , 18 23 , 29 , 31 , 35 , 36 , 39 , 42 , 54 , 61 , 76 ]. Some of these modified Aβ species are also observed in the brains of transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…People with DS also have an increased risk of developing early onset AD [29][30][31]. Interestingly the gene encoding APP is localized within a region of chromosome 21 that is critical for DS, and the triplication of the APP gene results in elevated levels of Aβ peptides that form amyloid plaques at least two decades prior to the onset of the clinical AD-like symptoms [31][32][33]. DS brains demonstrate Aβ plaques already at 12-30 year of age, principally in the form of diffuse Aβ plaques, the type of early Aβ pathology also seen at preclinical (i.e., pathological aging) and prodromal stages of sporadic AD [30,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional reviews explore neuroimaging of AD pathology in DS, including tau imaging (Rafii, ), imaging of cerebrovascular pathology (Carmona‐Iragui et al, ), and postmortem correlations of AD pathology to amyloid PET imaging (Abrahamson et al, ). Biomarkers are also a central theme of the reviews by Petersen and O'Bryant (2019) who explored the current state on the literature of blood‐based biomarkers found in individuals with DS, particularly those with AD or prodromal AD and by Alhajraf, Ness, Hye, & Strydom () who conducted meta‐analyses of studies comparing plasma amyloid beta (Aβ) levels between DS individuals and controls, and between DS individuals with and without dementia.…”
mentioning
confidence: 99%